Evaluating the Performance of Cuba's Sugarcane Basic Units of Cooperative Production During Their First Decade - José Alvarez (EDIS, 2005)
The objective of this fact sheet is to provide a performance evaluation of the sugarcane UBPCs after their first ten years in operation. The evaluation follows standard measures such as production/productivity, revenue, cost, and profitability. It also revises the accomplishments of the UBPCs relating to their original goals and objectives. The fact sheet ends with a discussion of some of the factors that appear to be limiting the efficiency and profitability in Cuba's sugarcane UBPCs. As opposed to what was the norm in the past, comprehensive official data from Cuba's Ministry of Sugar (MINAZ) have recently become available for these cooperatives (MINAZ, 2003). This is EDIS document FE562, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published June 2005.